2020
DOI: 10.1111/bjh.17026
|View full text |Cite|
|
Sign up to set email alerts
|

The role of eosinophil morphology in distinguishing between reactive eosinophilia and eosinophilia as a feature of a myeloid neoplasm

Abstract: Summary Morphological features of eosinophils in patients with reactive eosinophilia (28 patients) and clonal eosinophilia (26 patients) have been compared with each other and with the eosinophil characteristics of healthy volunteers (three subjects) and of patients with the idiopathic hypereosinophilic syndrome (three patients). Morphological features, assessed in isolation from other haematological abnormalities, were found to have poor specificity for a myeloid neoplasm. The most useful feature was the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…A systematic study comparing reactive and neoplastic cases reported that, although there was a tendency to more marked morphological abnormalities in those with clonal neoplastic eosinophils, there was considerable overlap. 1 The feature most strongly associated with neoplasia, particularly because of its association with inv( 16), was the presence of immature basophilic granules but as demonstrated in this patient, even this is not specific for neoplasia.…”
mentioning
confidence: 53%
“…A systematic study comparing reactive and neoplastic cases reported that, although there was a tendency to more marked morphological abnormalities in those with clonal neoplastic eosinophils, there was considerable overlap. 1 The feature most strongly associated with neoplasia, particularly because of its association with inv( 16), was the presence of immature basophilic granules but as demonstrated in this patient, even this is not specific for neoplasia.…”
mentioning
confidence: 53%
“…68 In contrast, eosinophil morphology in isolation has poor specificity for a myeloid neoplasm. 69,70 Lymphocyte-variant HE is a more obscure diagnostic entity characterized by an abnormal T-cell population demonstrated by flow immunophenotyping, which may be associated with excessive eosinophilopoietic cytokine production in vitro (eg, serum IL-5). 21,71,72 If none of the aforementioned conditions is identified, a diagnosis of idiopathic HES is made if organ damage is present, and a diagnosis of idiopathic HE is rendered if organ compromise is not found.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Previous reports have been called either acute eosinophilic leukemia (AEL) or acute myeloid leukemia with eosinophilia [ 10 , 11 ]. Eosinophil dysplasia has been noted in both benign and neoplastic disorders but may be helpful in the differential diagnosis of potential myeloid neoplasms [ 12 ]. We prefer the term AEL as being consistent with other AML subtypes.…”
Section: Discussionmentioning
confidence: 99%